2016
DOI: 10.15547/bjvm.898
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among circulating metabolic biomarkers in healthy high-producing holstein dairy cows in different physiological states

Abstract: Information regarding metabolic profile in different physiological sates of dairy cows can assist veterinarians to monitor the herd health and productive performance. Furthermore, the relationships among the metabolic parameters can be used to detect the effect of each parameter on another one. The aim of the current research was to clarify the interactions among metabolic parameters in different physiological states of high producing Holstein dairy cows. The present study was carried out on 25 multiparous Hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The increase in the plasma concentration of TG of glycerol-treated cows was consistent with the increase in glucose synthesis, which enhanced the animal's energy, which positively affected the increase in liver activity in the synthesis of TG and its excretion outside the liver as VLDL (34), or it may be due to the inclusion of glycerol other reasor metabolism process that may result in TG synthesis, as glycerol is the backbone of triglycerides (4). In addition, the increase of glucose in the blood, is positively correlated with the concentration of TG (10,13), as glucose is an important source of carbon in the synthesis of fatty acids (18). The decrease concentration of cholesterol affected by the addition of glycerol may be due to an increase in the body's energy through the positive effect of glycerol in promoting the process of gluconeogenesis (34), since the availability of glucose is elevated, animals are minimally mobilized their body fat for generating energy thus lowering blood cholesterol (44).…”
Section: Results and Discussion Milk Yield And Componentsmentioning
confidence: 99%
“…The increase in the plasma concentration of TG of glycerol-treated cows was consistent with the increase in glucose synthesis, which enhanced the animal's energy, which positively affected the increase in liver activity in the synthesis of TG and its excretion outside the liver as VLDL (34), or it may be due to the inclusion of glycerol other reasor metabolism process that may result in TG synthesis, as glycerol is the backbone of triglycerides (4). In addition, the increase of glucose in the blood, is positively correlated with the concentration of TG (10,13), as glucose is an important source of carbon in the synthesis of fatty acids (18). The decrease concentration of cholesterol affected by the addition of glycerol may be due to an increase in the body's energy through the positive effect of glycerol in promoting the process of gluconeogenesis (34), since the availability of glucose is elevated, animals are minimally mobilized their body fat for generating energy thus lowering blood cholesterol (44).…”
Section: Results and Discussion Milk Yield And Componentsmentioning
confidence: 99%
“…The decrease in the concentration of NEFA in the blood may be due to the positive effect of glycerol in improving the animal's energy, which may enhance the activity of the liver in increasing the absorption of NEFA from the blood and its esterification into triglycerides and then its release outside the liver in the form of VLDL, which results in a decrease in the concentration of NEFA and then a decrease in BHBA formation (21). The decrease in the concentration of NEFA and BHBA was consistent with the increase in blood glucose concentration as a result of their association (NEFA and BHBA) in a negative relationship with glucose concentration (r = -0.362 and r = -0.77, respectively) (18,10). This result is consistent with the result of the study of Burakowska et al (9), which showed that adding glycerol to the starter diet of Holstein calves reduced the concentration of both NEFA and BHBA in the blood of calves.…”
Section: Blood Characteristicsmentioning
confidence: 85%
“…No. 02160) -Cholesterol concentration was measured by enzymatic methods (4), using kit of BIOLABO, France (Cholesterol CHOD PAP) -Triglyceride concentration was measured by Enzymatic hydrolysis ( 16) associated with oxidative reaction (44), using kit of BIOLABO, France (Triglyceride GPO Method) -Non-esterified fatty acids (NEFA) was measured by Enzymatic Colorimetric Method (10), using kit of MyBioSource ,USA (Cat. No.…”
Section: -Blood Samplesmentioning
confidence: 99%
“…The results showed in Table (2) that there was a significant increase (P≤0.05) in the glucose concentration in the BCS2 group, which amounted to 62.19 ± 1.34 mg / 100 ml compared to the BCS3 group, which amounted to 57.86 ± 0.84 mg / 100 ml, while the glucose concentration was 59.30 ± 1.24 mg /100ml in BCS1 group, whose concentration did not differ significantly in this group with its concentration in BCS2 or BCS3 group.The increase in glucose concentration may be attributed to the increase in the intake of dry matter and the improvement of the cow's energy, which leads to an increase in the level of insulin, and thus a decrease in the breakdown of fats from adipose tissues, and the concentration of NEFA in the blood decreases, and the concentration of BHB decreases accordingly, which is the source of NFEA. [39], as the correlation coefficient is r = 0.850 between the concentration of NEFA and the concentration of BHB in the blood [40] or the reason for the high glucose concentration when increasing cow energy is to enhance the effectiveness and vitality of the liver In the uptake of NEFA from the blood, their re-esterification into triglycerides, and their release out of the liver as low-density lipoproteins [41], In the early lactation, increased dry matter intake leads to an increase in the production and availability of glucose-forming raw materials such as propionate from rumen ferments [42,43]. As for the lower blood glucose concentration in cows with a higher body condition scor at calving, it may be attributed to the fact that these cows suffered before calving from a decrease in dry matter intake compared to cows with a medium or lower body condition scor [44][45][46][47] and this leads to a decreased supply of exogenous glucose and the noncarbohydrate feedstock involved in gluconeogenesis [48], This situation is exacerbated by the high demand for energy in the final stage of pregnancy to meet the growing needs of the fetus for the purpose of growth and the high demand for energy after calving for the purpose of production [49].…”
Section: Relationship Of Body Condition Score With Some Blood Metabol...mentioning
confidence: 99%
“…Perhaps the high concentration of glucose is due to an increase in dry matter intake and an increase in energy level, which leads to an increase in insulin concentration, and accordingly the breakdown of fat from adipose tissue, the source of fatty acids, decreases. non-esterified blood, as well as a decrease in the concentration of BHB [39], and the correlation coefficient (r=0.850) between the concentration of these two metabolites in the blood [40], In addition, the increase in the concentration of glucose and the improvement in the energy of the cow lead to enhancing the effectiveness of the liver in absorbing NEFA from the blood and releasing them outside the liver in the form of low-density lipoproteins after their esterification into triglycerides [41]. Also, during early lactation the increased intake of dry matter leads to an increase in the supply of energy to the rumen, and thus the availability of raw materials resulting from rumen fermentations, such as propionate, which is one of the raw materials involved in the creation of glucose [42,43].…”
Section: Relationship Of Body Condition Score With Some Blood Metabol...mentioning
confidence: 99%